2022
DOI: 10.1371/journal.pone.0272294
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput integrated biofilm-on-a-chip platform for the investigation of combinatory physicochemical responses to chemical and fluid shear stress

Abstract: Physicochemical conditions play a key role in the development of biofilm removal strategies. This study presents an integrated, double-layer, high-throughput microfluidic chip for real-time screening of the combined effect of antibiotic concentration and fluid shear stress (FSS) on biofilms. Biofilms of Escherichia coli LF82 and Pseudomonas aeruginosa were tested against gentamicin and streptomycin to examine the time dependent effects of concentration and FSS on the integrity of the biofilm. A MatLab image an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In their recent study, Nguyen et al utilized a high-throughput microfluidic platform to investigate the combined effects of antibiotic concentration and fluid shear stress on biofilms. Their findings underscored the nuanced responses of biofilms to these factors, depending on bacterial species and environmental conditions, highlighting the pivotal role of shear stress in directing biofilm evolution in bioelectrochemical systems [12]. Pham et al found that applying a shear rate of 120 s −1 (approximately 120 mPa) resulted in increased power production of MFCs compared to a shear rate of 0.3 s −1 (approximately 0.3 mPa) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In their recent study, Nguyen et al utilized a high-throughput microfluidic platform to investigate the combined effects of antibiotic concentration and fluid shear stress on biofilms. Their findings underscored the nuanced responses of biofilms to these factors, depending on bacterial species and environmental conditions, highlighting the pivotal role of shear stress in directing biofilm evolution in bioelectrochemical systems [12]. Pham et al found that applying a shear rate of 120 s −1 (approximately 120 mPa) resulted in increased power production of MFCs compared to a shear rate of 0.3 s −1 (approximately 0.3 mPa) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, microfluidic devices have paved the way for studying the combined effect of reactor geometry and hydrodynamic conditions in a high-throughput manner. 16,17 Such a lab-on-a-chip device is also of great merit to precisely emulate the biological phenomenon on-line since its closed system design is able to cover a wide range of velocities applied to deposited cells without risking any unintended environmental effects. 18…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, microfluidic devices have paved the way for studying the combined effect of reactor geometry and hydrodynamic conditions in a high-throughput manner. 16,17 Such a lab-ona-chip device is also of great merit to precisely emulate the biological phenomenon on-line since its closed system design is able to cover a wide range of velocities applied to deposited cells without risking any unintended environmental effects. 18 Therefore, the primary objective of this study is to employ a microfluidic device to evaluate the degree of cell detachment from fully-seeded supporting materials immersed in a flowing medium under varying shear liquid forces.…”
Section: Introductionmentioning
confidence: 99%
“…Previous platforms using simple diffusion have produced continuous concentration gradients of antimicrobials 33,34 , but these approaches present a problem in determining the minimum inhibitory concentration (MIC) precisely. More recent platforms were successful at generating concentration gradients that are linear [33][34][35][36][37] ,logarithmic 35 , or sigmoidal 38 . Nevertheless, these techniques employ unstandardized concentration gradients.…”
Section: Introductionmentioning
confidence: 99%